2015
DOI: 10.7836/kses.2015.35.4.067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on thermal & electrical characteristics variation of PV module with damaged bypass diodes

Abstract: : PV module is conventionally connected in series with some solar cell to adjust the output of module. Some bypass diodes in module are installed to prevent module from hot spot and mismatch power loss. However, bypass diode in module exposed outdoor is easily damaged by surge voltage. In this paper, we study the thermal and electrical characteristics change of module with damaged bypass diode to easily find module with damaged bypass diode in photovoltaic system consisting of many modules. Firstly, the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Therefore, the annual degradation rate by the failed bypass diode was about 11% or 25% depending on the climatic conditions [25]. A bypass diode fault results in an output loss due to a decrease of the open circuit voltage because the potential (voltage) difference of strings connected with a failed bypass diode is about 0 V. Additionally it elevates the surface temperature of the solar cells in the PV module, thereby resulting in the lower performance of the PV power plant [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the annual degradation rate by the failed bypass diode was about 11% or 25% depending on the climatic conditions [25]. A bypass diode fault results in an output loss due to a decrease of the open circuit voltage because the potential (voltage) difference of strings connected with a failed bypass diode is about 0 V. Additionally it elevates the surface temperature of the solar cells in the PV module, thereby resulting in the lower performance of the PV power plant [26].…”
Section: Introductionmentioning
confidence: 99%
“…A short circuit of the SD does not have devastating consequences, but it leads to a decrease in output due to the withdrawal of part of the solar cells of the SP and accelerates their degradation (W. G. Shin et al, 2018), (Davarifar et al, 2013), (W.-G. Shin et al, 2015). Among the methods for diagnosing malfunctions of stepper motors as part of the joint venture, the following methods can be distinguished: visual inspection (Köntges М, 2014); method of thermal imaging diagnostics (Kato, 2011), (Köntges М, 2014); analytics of current-voltage characteristics (CVC) of the joint venture (Ziar et al, 2014), (Köntges М, 2014), (Davarifar et al, 2013), (Dhimish M, 2017); various variations and syntheses of the above methods (for example, thermal imaging diagnostics using an external source) (Tsanakas et al, 2017), (Köntges et al, 2009).…”
Section: Operation Of the Shunt Diode Under Different Conditionsmentioning
confidence: 99%
“…In this regard, there is a study that released which changes in the electrical property at PV module caused by a failure of the bypass diode (shown as F6 in Figure 2). The failure bypass diodes lose their properties of forward and reverse bias to become a micro-resistance, and are in a short circuit state with solar cells that are connected to a fault bypass diode [12,15,16]. Furthermore, recent research reported, when the bypass diode is shorted failure while the PV system is stopped, the temperature of a junction box increases [12].…”
Section: Bypass Diode Faultmentioning
confidence: 99%